Productivity of a plantation of asparagus (Asparagus officinalis var. Altilis) initiated green seedlings over four growing seasons - Castagnino, A M; Díaz, K E; Rosini, M B; Marina, J (Revista Bio Ciencias, 2014)
Although there are two initiation systems for an asparagus crop, i.e. by means of crowns and by means of seedlings, only the former allows the initiation of the definitive plantation in the first year. In order to determine the incidence of the seedling size throughout the first six years since planting, a trial was started on august 21, 2002, with three cell sizes: PG: big, PM: medium and PCH: small (70, 50 and 20 cm3 respectively) and two densities: D1:35,714 and D2: 17,857 pl.ha-1, using the hybrid UC-157 and evaluating its productivity in the period 2005-2008. Fresh weight per harvest (PFC) and total annual fresh weight per ha (PFT), number of turions per harvest (NTC) and per ha (NT) and average weight per turion (PPT) were determined. The PTF 2005-2008 was 26.300 Kg ha-1 and NT, with an annual average of 6,575 Kg ha-1 and 480,180 turions, respectively. NT showed a growing tendency throughout the whole period. Whereas, while the PFT grew in 2005-2007, it decreased in 2008 due to lower PPT, caused possibly by intra-specific competition. PM allowed a greater yield PFC: 343 Kg ha-1. The PPT turned out to be similar to that in 2005-2007, however it decreased in 2008. D1 obtained the maximum yield throughout the whole period. It can be concluded that when the aim is to obtain high initial productivity, it would be advisable to use seedlings of good size. Besides, the choice of density is an important factor due to the fact that there seems to be a direct relationship between the planting frame used and the obtained productivity.